2016
DOI: 10.3389/fpubh.2016.00182
|View full text |Cite
|
Sign up to set email alerts
|

Blood Levels of Monoamine Precursors and Smoking in Patients with Schizophrenia

Abstract: Smoking is highly prevalent in patients with schizophrenia and exerts a negative impact on cardiovascular mortality in these patients. Smoking has complex interactions with monoamine metabolism through the ability of cigarette smoke to suppress Type 1 T helper cell (Th1) type immunity, the immunophenotype that is implicated in phenylalanine hydroxylase (PAH) dysfunction and tryptophan (Trp) breakdown to kynurenine (Kyn) via indoleamine 2,3-dioxygenase. Nicotine also induces tyrosine hydroxylase (TH) gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
3
3
Order By: Relevance
“…Differences in amino acid levels did not remain significant after adjustment for smoking status. Conflicting data on the effect of smoking on monoamine metabolism ( 42 44 ) and the high proportion of smokers in our patient group vs. the low proportion in controls make the interpretation of these results difficult.…”
Section: Discussioncontrasting
confidence: 60%
“…Differences in amino acid levels did not remain significant after adjustment for smoking status. Conflicting data on the effect of smoking on monoamine metabolism ( 42 44 ) and the high proportion of smokers in our patient group vs. the low proportion in controls make the interpretation of these results difficult.…”
Section: Discussioncontrasting
confidence: 60%
“… 52 An inhibitory effect of smoking on IDO has been reported and subsequent decreases KYN concentrations. 53 , 54 Even though, it is suggested that IDO activity is reduced by smoking, no increased TRP concentrations were found in the present study or in previous studies. 53 , 54 …”
Section: Discussioncontrasting
confidence: 86%
“…Naz et al found that in chronic obstructive pulmonary disease (COPD) patients, the level of kynurenine, which is the main product of tryptophan [ 44 ], decreased in smokers relative to never-smokers [ 38 ]. Mathai et al [ 45 ] reported that in schizophrenic patients, current smokers showed lower kynurenine levels than past smokers, which further elucidates the neurobiological underpinnings of altered kynurenine levels in smokers. In these studies, there were non-significant decreases in tryptophan levels.…”
Section: Discussionmentioning
confidence: 99%